The Bhagirathi-Hooghly Basin : proceedings of the Interdisciplinary Symposium - Bagchi, Kanangopal; Munsī, Sunīla, 1922-; Bhattacharyya, R. N. (S. Kanjilal, 1972)
On geologicalm hydrological, and economic development in Bihar and West Bengal.